2014
DOI: 10.1371/journal.pone.0089334
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Availability Regulates Virulence Gene Expression in Streptococcus suis

Abstract: Streptococcus suis is a major bacterial pathogen of young pigs causing worldwide economic problems for the pig industry. S. suis is also an emerging pathogen of humans. Colonization of porcine oropharynx by S. suis is considered to be a high risk factor for invasive disease. In the oropharyngeal cavity, where glucose is rapidly absorbed but dietary α-glucans persist, there is a profound effect of carbohydrate availability on the expression of virulence genes. Nineteen predicted or confirmed S. suis virulence g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 88 publications
(83 reference statements)
1
84
0
Order By: Relevance
“…This might be due to higher expression of suilysin, the pore-forming toxin produced by most pathogenic strains of S. suis , which is carbon catabolite repressed by glucose when grown in vitro [44]. …”
Section: Discussionmentioning
confidence: 99%
“…This might be due to higher expression of suilysin, the pore-forming toxin produced by most pathogenic strains of S. suis , which is carbon catabolite repressed by glucose when grown in vitro [44]. …”
Section: Discussionmentioning
confidence: 99%
“…More precisely, catabolite control protein A (CcpA) has been shown to modulate the expression of virulence features, including CPS, under conditions of high glucose availability . It has also been proposed that at the porcine upper oropharyngeal niche, the high ratio of starch to glucose promotes a significant change on S. suis gene transcription, including those putatively involved in epithelial cell interactions . Again, more studies on the role of the environment on a possible down‐regulation of the CPS and/or up‐regulation of the expression of adhesins, with a consequent increase of adhesion to epithelial cells, should be done to confirm such hypotheses.…”
Section: How Does Streptococcus Suis Establish In Mucosa and Breakdowmentioning
confidence: 99%
“…The decreased lethality and the absence of bacterial blood loads of pigs after intranasal experimental infection with the Δiga mutant strain suggested that mucosal IgA would play a crucial role in resistance to S. suis invasion of mucosal barriers and dissemination in the naïve host . In addition, an association between in vitro up‐regulation of the iga gene expression and the increase in adhesion/invasion of pig tracheal epithelial cells has recently been observed . However, in healthy animals, the presence of specific or cross‐reactive IgA against S. suis, which might explain the lack of virulence of such a mutant, has not been tested.…”
Section: How Does Streptococcus Suis Fight Against Early Host Immune mentioning
confidence: 99%
See 1 more Smart Citation
“…The link between carbohydrate utilization and virulence has been studied in pathogens, like group A streptococci (GAS), or more recently in Streptococcus suis using transcriptome analyses or mouse oropharynx colonization experiments (1,31). The combined results demonstrate that maltodextrin acquisition is likely to be a key factor in the ability of GAS to successfully infect the oropharynx.…”
Section: Substratementioning
confidence: 99%